2000
DOI: 10.1021/es000908p
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Benzene in a Stratified Lake Receiving Contaminated Groundwater Discharges from a Superfund Site

Abstract: Predicting the fate of benzene in aquatic environments, and estimating corresponding human exposures, is critically dependent on knowledge of this carcinogen's biodegradation rate under the site-specific conditions. We used three approaches for quantifying this key fate process: (1) shortterm (hours) observations of benzene loss in laboratory incubations of representative water samples, (2) wholelake benzene mass balance studies, and (3) modeling of the temporal evolution of benzene vertical profiles in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Lake Mishwam is methanogenic. A sharp density contrast maintains permanently anaerobic conditions and stratification is preserved during all but the most extreme weather systems (Wick et al ., 2000). Methane is oxidized at the chemocline boundary, and aerobic methanotrophs (γ‐ and α‐proteobacteria) are found in the water column (M. Fisher, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lake Mishwam is methanogenic. A sharp density contrast maintains permanently anaerobic conditions and stratification is preserved during all but the most extreme weather systems (Wick et al ., 2000). Methane is oxidized at the chemocline boundary, and aerobic methanotrophs (γ‐ and α‐proteobacteria) are found in the water column (M. Fisher, pers.…”
Section: Discussionmentioning
confidence: 99%
“…It also is possible that these samples contain particulate material mixed in from deeper waters. Although the lake stratification is extreme (surface water residence time a few days, deep water residence time > 100 days; Wick et al ., 2000) some cross‐chemocline mixing must occur. Quantitative PCR and comparisons between surface and deep waters may resolve this question in the future.…”
Section: Discussionmentioning
confidence: 99%
“…6. Bottom water known to be anoxic and to contain methane [24] was collected for this experiment in a BOD (biochemical oxygen demand) bottle from the Mishawum Lake (also known as Halls Brook Storage Area) in the Aberjona River watershed, north of Boston, MA, USA. Intermediate points in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the model predictions with data from a lake and reservoir in California, the researchers showed that the maximum half-life of MTBE is less than forty days under calm conditions and approximately six days when the average wind speed is more than ten miles per hour. To investigate the fate of benzene in a stratified lake located next to a superfund site, Wick et al (2000) used three approaches: shortterm (hours) observations of benzene decay under laboratory conditions, entire-lake benzene mass balance calculations, and temporal evaluation of benzene vertical profiles modeling in the lake. The calculations showed that the metalimnion was the main sink for the benzene, and about 80% of the benzene received by the lake was degraded during the water residence.…”
Section: Modelsmentioning
confidence: 99%